1994
DOI: 10.1111/j.1600-0773.1994.tb01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoperoxidative Damage on Lead Exposure in Rat Brain and its Implications on Membrane Bound Enzymes

Abstract: We have investigated the effect of lead exposure on lipid peroxidation, a deteriorative process of the membranes, in the different regions of the brain. Lead treatment (50 mg/kg b.wt. intragastrically) for a period of eight weeks to rats resulted in a significant accumulation of lead in all the regions of brain, at maximum in hippocampus. The lipid peroxidation was accentuated following lead exposure and there was a linear correlation between the increase in lipid peroxidation and increase in lead levels (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
76
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(96 citation statements)
references
References 26 publications
17
76
2
1
Order By: Relevance
“…Our previous studies (Ercal et al 1996;Gurer et al 1998Gurer et al , 1999a as well as the present one support the hypothesis indicated by several other groups (Ribarov and Bochev 1982;Ito et al 1985;Monterio et al 1985Monterio et al , 1991Lawton and Donaldson 1991;Sandhir et al 1994;Solliway et al 1996) that Fig. 2.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies (Ercal et al 1996;Gurer et al 1998Gurer et al , 1999a as well as the present one support the hypothesis indicated by several other groups (Ribarov and Bochev 1982;Ito et al 1985;Monterio et al 1985Monterio et al , 1991Lawton and Donaldson 1991;Sandhir et al 1994;Solliway et al 1996) that Fig. 2.…”
Section: Discussionsupporting
confidence: 92%
“…In general, ROS are involved in impairing the polyunsaturated fatty acids of the membrane phospholipids of the cells causing defects of cellular functions (Halliwell and Gutteridge, 1985). Pb exposure was also related with tissue oxidative damage in chicks (Donaldson and Leeming, 1984) and rats (Sandhir et al, 1994).…”
Section: Leadmentioning
confidence: 99%
“…Ratos tratados com chumbo mostraram diminuição dos níveis séricos de glutationa (Alexander et al, 1986), composto que poderia estar envolvido nos mecanismos de defesa contra as espécies reativas de oxigênio geradas pelo chumbo. Índices de correlação positiva entre TBARS e concentração sangüínea de chumbo foram obtidos no grupo controle (r=0,602) e no de atiradores indoor (r=0,432), corroborando resultados obtidos em ratos tratados com chumbo (Sandhir et al, 1993;Neal et al, 1998;Adonaylo e Oteiza, 1999;Gurer et al, 1999), em trabalhadores de minas de chumbo (Ye et al, 1999) e em indivíduos com concentrações sangüíneas de chumbo superiores a 35µg/dL (Jiun e Hsien, 1994). O chumbo inibe a biossíntese do heme, resultando num acúmulo de ALA, que, em pH fisiológico, autoxida-se, levando à formação de radical superóxido (O (Halliwell e Gutteridge, 2000).…”
Section: Resultsunclassified